LOCAL CHURCHES OWNED BUSINESS AS STRATEGIC TOWARD SUSTAINABILTY AND FINANCIAL OTONOMY - Cristi Devi Darnita (APOSTOLOS, 2023)
The purpose of this paper is to describe and analyze the strategy of local churches, in this case, tribal churches that exist in GKE Resort Tewah, for sustainability and financial independence by building businesses owned by the church. The method used is exploratory qualitative with observation, interview, and documentation study techniques. This paper concluded that the church, as a non-profit organization, can build a business to support church finances. Local churches build businesses as one of the church's financial management strategies sourced from the empowerment of church assets. Empowerment of local church assets is classified as a business in the form of investment in property assets included in non-current assets. Income from church-owned businesses is recognized and recorded as general church income so that the income is used to fund church operations. Business ownership by local churches today can be one of the strategies to achieve the financial independence of the church and the sustainability of local churches that depend on the offerings given by the congregation.